Population trends of insect pollinators in a species-rich tropical rainforest: stable trends but contrasting patterns across taxa - Bonadies, Ernesto; Lamarre, Greg P A; Souto-Vilarós, Daniel; Pardikes, Nicholas A; Silva, José Alejandro Ramírez; Perez, Filonila; Bobadilla, Ricardo; Lopez, Yacksecari; Basset, Yves (Biology letters, 2024)
Recent reports of insect decline have raised concerns regarding population responses of ecologically important groups, such as insect pollinators. Additionally, how population trends vary across pollinator taxonomic groups and degree of specialization is unclear. Here, we analyse 14 years of abundance data (2009-2022) for 38 species of native insect pollinators, including a range of Coleoptera, Lepidoptera and Hymenoptera specialists and generalists from the tropical rainforest of Barro Colorado Island, Panama. We estimated population trends across taxonomic groups to determine whether specialist species with a narrower range of interacting mutualistic partners are experiencing steeper population declines under environmental change. We also examined the relationship between climate variables and pollinator abundance over time to determine whether differences in sensitivity to climate predict differences in population trends among pollinator species. Our analyses indicated that most pollinator populations were stable or increasing, with few species showing evidence of decline, regardless of their degree of specialization. Differences in climate sensitivity varied among pollinator species but were not associated with population trends, suggesting other environmental factors at play for tropical insect pollinators. These results highlight the need for long-term population data from diverse tropical taxa to better assess the environmental determinants of insect pollinator trends.
Keywords: bee; Pollination; hmyz; Rainforest; Population Dynamics; pollinator decline; long-term monitoring; butterfly; zvířata; deštný prales; Insecta; klimatické změny; populační dynamika; Panama; tropické klima; climate change; Climate Change; Tropical Climate; Animals; opylení; beetle